2023
DOI: 10.1039/d2fo02523j
|View full text |Cite
|
Sign up to set email alerts
|

Thyme (Thymus vulgaris L.) polyphenols ameliorate DSS-induced ulcerative colitis of mice by mitigating intestinal barrier damage, regulating gut microbiota, and suppressing TLR4/NF-κB-NLRP3 inflammasome pathways

Abstract: Thyme (Thymus vulgaris L.) is an important medicinal and edible homologous plant, and the composition and bioactivity of its polyphenol extracts have attracted widespread attention from researchers. In this study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…6,13,31 Previous studies have shown that certain natural polyphenol compounds (e.g., lychee pulp phenolics and thyme polyphenols) could alleviate the DSS-induced inflammatory response by inactivating the TLR4-mediated NF-κB signaling pathway and NLRP3 inflammasome, thereby protecting the intestinal barrier function. 23,32 In this study, SEA was found to upregulate TLR4-related proteins both in vivo and in vitro. It was speculated that SEA could activate TLR4 signal transduction directly or by stimulating LPS production in vivo, which might lead to the stronger toxicity of SEA on intestinal homeostasis, thus attracting widespread attention in the field of food safety.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…6,13,31 Previous studies have shown that certain natural polyphenol compounds (e.g., lychee pulp phenolics and thyme polyphenols) could alleviate the DSS-induced inflammatory response by inactivating the TLR4-mediated NF-κB signaling pathway and NLRP3 inflammasome, thereby protecting the intestinal barrier function. 23,32 In this study, SEA was found to upregulate TLR4-related proteins both in vivo and in vitro. It was speculated that SEA could activate TLR4 signal transduction directly or by stimulating LPS production in vivo, which might lead to the stronger toxicity of SEA on intestinal homeostasis, thus attracting widespread attention in the field of food safety.…”
Section: Discussionmentioning
confidence: 57%
“…Remarkably, intestinal barrier dysfunction and bacterial translocation are often accompanied by inflammation. , Inflammatory reactions can also further aggravate intestinal barrier damage. , The activation of the pattern recognition receptor TLR4 (responsible for recognizing and binding to LPS) is closely related to intestinal barrier damage, inflammatory response, and even immune system dysfunction . The overactivation of the TLR4 pathway can further activate downstream inflammation-related signaling pathways, such as NF-κB, MAPKs, and NLRP3 inflammasome, which leads to the maturation and release of the proinflammatory cytokines (IL-18 and IL-1β) and plays a crucial role in the progression of inflammatory intestinal barrier injury. ,, Previous studies have shown that certain natural polyphenol compounds (e.g., lychee pulp phenolics and thyme polyphenols) could alleviate the DSS-induced inflammatory response by inactivating the TLR4-mediated NF-κB signaling pathway and NLRP3 inflammasome, thereby protecting the intestinal barrier function. , In this study, SEA was found to upregulate TLR4 - related proteins both in vivo and in vitro . It was speculated that SEA could activate TLR4 signal transduction directly or by stimulating LPS production in vivo , which might lead to the stronger toxicity of SEA on intestinal homeostasis, thus attracting widespread attention in the field of food safety.…”
Section: Discussionmentioning
confidence: 99%
“…LPS produced by them as one of the most common endotoxins and directly activates TLR4, which further leads to the activation and release of NF-κB-related factors into the nucleus and activates the expression of target genes involved in cell proliferation and apoptosis. 37 Another experimental colitis model study demonstrated that the prescription medications SASP work as NF-κB inhibitors to ameliorate UC. 22 According to our research, SASP or DOP may have anticolitic effects by partially inhibiting the activation of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the body with an impaired colonic barrier, it is unable to block the invasion of harmful bacteria, including some Gram-negative bacteria. LPS produced by them as one of the most common endotoxins and directly activates TLR4, which further leads to the activation and release of NF-κB-related factors into the nucleus and activates the expression of target genes involved in cell proliferation and apoptosis . Another experimental colitis model study demonstrated that the prescription medications SASP work as NF-κB inhibitors to ameliorate UC .…”
Section: Discussionmentioning
confidence: 99%
“…nal microbiota, thereby preventing and treating IBD and related colon cancers. 113,114 Inhibition of colitis can also be achieved through different signaling pathways. Broccoliderived nanoparticles (BDN) activate adenosine monophosphate-activated protein kinase (AMPK) in dendritic cells (DCs), 115 exosome-like nanoparticles from mulberry bark (MBELN) promote the aryl hydrocarbon receptor (AHR) signaling pathway mediated by heat shock protein family A (Hsp70) member 8 (HSPA8), 116 and turmeric-derived nanoparticles (TDNPs 2) mediate the inactivation of the nuclear factor kappa B (NF-κβ) pathway.…”
Section: Food and Function Reviewmentioning
confidence: 99%